Extradição de nacionais e o julgamento pelo Tribunal Penal Internacional - Grégio, Grécio Nogueira (2008)
The present dissertation develops an analysis of the principle of extraction of citizens seen from the focus of an international penal jurisdiction, mainly the one established by the International Criminal Court. It analysis the topics related to the founding of the ICC including its historical background, how the international treaties were incorporated by the law codes of each member country. It develops analysis about the basic knowledge related to the fundamental rights aiming at clearing conflicts within the codes of law. It also deals with the problems related to the well-legal criminal specially the transnational crimes. Considering the theoretical references, this dissertation tries do solve the conflict between the fundamental rights code with the character of principle. It develops an empirical research based on data collected in the archives of Supreme Court, about the existence of extraditional demands against brazilian citizens in the period between 1911 and 1934. It analyses the law 2416 of 1911 which specifically allowed the extradition of brazilian citizens. It discusses the jurisprudence of the Supreme Court up to 1934, when the constitutional restrictions to the extradition of brazilian citizens came into effect. It analysis situations of comparative rights when it was understood the surrending principle, pointing out and making comments on the changes of the law including the ones in the constitution. It develops perspectives based on the solutions already adopted by the brazilian lawmen, specifically by the Supreme Court, as well as the Congress, whether by the appliance of the extraterritoriability or by the incorporation of the treaty which created the ICC. It points out the risks for Brazil, concerning the non appliance of measures concerning cooperation with International Criminal Court.